Deregulation and Schedule Competition in Simple Airline Networks - Youdi Schipper; Piet Rietveld; Peter Nijkamp (European Regional Science Association (ERSA), 1998)
The present paper investigates the choice of route network, frequencies and ticket prices in air transport networks served by oligopolists. The paper describes these choices in a simple airline network by means of a simulation model. Airline competition is modeled as a 2 stage game: airlines first choose a particular flight schedule in a network, and in the second stage, airlines choose ticket prices. This simulation model thus describes airline profit maximizing behaviour in a given network environment. The model may now serve as a basis to address particular policy related questions. One such question is the welfare effect of airline deregulation. The welfare consequences resulting from the deregulation of airline markets have been investigated quite amply, both theoretically and empirically. In most cases, deregulation has been demonstrated to confer substantial benefits to consumers, and in some cases also to producers. At the same time, however, the external costs associated with aviation have become a major public policy concern in many countries. External effects - which in this case include noise, emissions and congestion - arise when markets lack: resources like peace and quiet, clean air and space are often unpriced. As a result, these resources are used in quantities beyond a social optimum. In the context of airline deregulation, it is now interesting to analyze the welfare effects caused the process of airline deregulation, taking the external costs of aviation into account. The present paper addresses this question while the network character of air transportation is taken into account.
Keywords: 330